2018
DOI: 10.1186/s12961-018-0360-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on academic research productivity of postgraduate students in low- and middle-income countries

Abstract: BackgroundWhile several individual studies addressing research productivity of post-graduate students are available, a synthesis of effective strategies to increase productivity and the determinants of productivity in low-income countries has not been undertaken. Further, whether or not this research from post-graduate students’ projects was applied in evidence-informed decision-making was unknown. Therefore, we conducted a systematic review of literature to identify and assess the effectiveness of approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
22
0
4
Order By: Relevance
“…Similar studies in Nigeria and other parts of Africa have reported similar levels of RP and are at variance with the research output of academic faculty in HIC who produce more than 97% of the worlds’ research output. [ 10 11 12 13 ] For instance, a study among faculty at the Makerere University College of Health Sciences, Uganda, reported a PRP per capita of 2.1. [ 13 ] These findings have important implications for policy and planning as they highlight the need for university management to intensify efforts to improve RP and output among the researchers at CMUL and other institutions in LMIC in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in Nigeria and other parts of Africa have reported similar levels of RP and are at variance with the research output of academic faculty in HIC who produce more than 97% of the worlds’ research output. [ 10 11 12 13 ] For instance, a study among faculty at the Makerere University College of Health Sciences, Uganda, reported a PRP per capita of 2.1. [ 13 ] These findings have important implications for policy and planning as they highlight the need for university management to intensify efforts to improve RP and output among the researchers at CMUL and other institutions in LMIC in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our results reinforce the importance of patient-centred research, alongside operational research, for comprehending complex health conditions in developing countries and for improving the quality of care. CRs can play a significant role in identifying subjects that may be needed to link the knowledge gained in the field with policy and practice and inform clinical practice guidelines [ 18 , 19 ]. This reflects a more recent realisation that, while CRs may be low on the evidence-based medicine pyramid, they have a key role to play as a foundation of medical observation and often spur on further (statistical) research [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having the very first paper harshly rejected could add all the more to their lack of confidence. Obuku et al (2018) also find that confidence is a reason for low research productivity in low-middle income countries, as is the lack of use of postgraduate research in informing policy, along with poor supervision.…”
Section: Publication Challenges For Novice Journal Paper Authorsmentioning
confidence: 93%